Sự sẵn sàng học trực tuyến của sinh viên: Một nghiên cứu tại Trường Đại học Cần Thơ - Lữ, Quốc Vinh; Nguyễn, Thị Kim Lan; Nguyễn, Lam Vân Anh; Nguyễn, Ngọc Chi Lan (Tạp chí Giáo dục, 2025)
Amidst the dynamic shift toward digital transformation in higher education, evaluating students’ readiness for online learning has become both a theoretical and practical imperative. This study investigates the online learning readiness of 457 students from the Faculty of Foreign Languages, Can Tho University, across six key factors: learning conditions, technological confidence, self-directed learning, learning control, motivation, and online learning effectiveness. Findings reveal that students demonstrate a relatively high level of readiness (Mean = 3.51/5), with strong performance in learning conditions and motivation. However, limitations remain in areas such as learning control, confidence in using technology, and concentration. The study provides empirical evidence to inform curriculum adjustments, teaching method innovation, and policy planning aimed at enhancing students’ digital learning competence.